Floral induction (FI) in longan (Dimocarpus longan, Lour.) trees. III: Effect of shading the trees on potassium chlorate induced FI and resulting hormonal changes in leaves and shoots - Sringarm K. (2014)
Previous experiments demonstrated that treatment of longan trees with potassium chlorate (KClO3) induces "off season floral induction" (FI) even in the absence of the naturally required cool temperature [Manochai, P., Sruamsiri, P., Wiriya-alongkorn, W., Naphrom, D., Hegele, M., Bangerth, F., 2005. Year around off season flower induction in longan (Dimocarpus longan, Lour.) trees by KClO3 applications: potentials and problems. Sci. Hortic. 104, 379-390]. Potassium chlorate, however, cannot replace the presence of functional mature leaves and sufficient light intensity. Here we examined in more detail the effect of shade (about 10% of natural sunlight) on KClO3 affected hormone concentrations/transport of leaves and shoot apical buds (SAB) and their interactions with FI. Shade strongly inhibited/prevented KClO3-stimulated FI and this effect probably depended on light intensity. Vegetative flushes were delayed but not prevented by shading. On the other hand the export of IAA out of the SAB and, the leaf export of iP/iPA- and Z/ZR-type cytokinins were strongly inhibited. With the later hormones shade obviously acted synergistically with KClO3 to reduce this export. Comparable to the leaf export shade almost entirely prevented the strong increase in iP/iPA- and particularly Z/ZR-cytokinins in the SAB caused by KClO3 treatment. In spite of this inhibition of iP/iPA export out of leaves by shading, this cannot or not only be the mechanism by which shade prevented KClO3 induced off season FI because with few exceptions KClO3 by itself inhibited this iP/iPA export. However, shade inhibited the increase in CKs and here particularly Z/ZR cytokinins in the SAB and simultaneously prevented FI. Possible explanations about these contradictions are discussed. Certainly CKs are not the only hormones involved in the promotion or inhibition of FI of longan and other subtropical trees and the observed early and strong increase in IAA export of the SAB after KClO3 treatment may also be involved in the FI process. © 2009 Elsevier B.V. All rights reserved.